Factors Influencing Coaching Success: Role, Competence and Employee Engagement - Menara, Barbara (International Journal of Multidisciplinary Approach Research and Science, 2025)
This study investigated the factors influencing the effectiveness of workplace coaching interventions, focusing on the coach’s role, abilities, perceived coaching benefits, and engagement outcomes. Survey data from 73 participants in a UK sixth-form college were analyzed using Fisher’s exact test. The results indicate that managing negative emotions is more successful when coaching is conducted by external coaches or colleagues than by managers. A coach’s ability to lead conversations, maintain concentration, and avoid excessive personal opinions significantly affects the achievement of an individual target. Perceived coaching benefits such as overcoming workplace barriers and developing specific skills are strongly associated with coaching success. Engagement outcomes, including commitment to responsibilities and willingness to exert extra effort, were significantly related to coaching success in managing negative emotions and meeting individual goals. However, coaching success was not significantly associated with commitment to organizational goals. These findings suggest that organizations should carefully consider coach selection, emphasize potential coaching benefits, and tailor interventions to specific objectives to maximize the impact of coaching on employee engagement and performance. Further research with larger samples is recommended to validate these results and explore the transfer of coaching outcomes to workplace applications.